The mighty mahseers of the genera Tor, Neolissochilus and Naziritor: A review on resource distribution, biology, ecotourism and conservation - Sarma, Dr. Debajit; Dinesh Mohan; Ravindra Posti; Mukul Arya; Parvaiz Ahmad Ganie (Indian Journal of Fisheries, 2022)
Mahseers belonging to genus Tor, Neolissochilus and Naziritor, comprise important groups of food and sport fishes in the freshwater eco-systems. Tor mahseers being potential game fish are recognised as cultural icon in the pristine waters across the globe. They also have high nutritional value with high content of DHA, EPA and amino acids which are important to human health. Presently, 17 species of Tor, 25 species of Neolissochilus and 2 species of Naziritor have been reported and validated throughout the world. However, due to several anthropogenic and natural activities, their population is dwindling across most of the natural ecosystems and IUCN has categorised the group as endangered. Change in temperature and monsoon floods triggers the act of migration and spawning behaviour of mahseers in their respective ecological conditions. There are 47 species of mahseers in the world, out of which India harbours fifteen species. These species widely occur in the rocky and pristine fast flowing streams of India, China, Nepal, Sri Lanka, Myanmar, Malaysia, Thailand, Vietnam, Pakistan and Bangladesh. The present paper embodies the status of mahseers under the genera Tor, Neolissochilus and Naziritor to understand this magnificent group of fishes having extraordinary importance in terms of balancing aquatic biodiversity sustainability, creating opportunities for increasing livelihood though utilising this fish in sports (angling and ecotourism) and draws immediate attention for its conservation in inclusive and responsible manner. Keywords: Conservation, Ecotourism, GIS, Mahseer, Resource mapping